QUALITY CULTURE THROUGH THE IMPLEMENTATION OF MBNQA QUALITY MANAGEMENT AND ITS RELATION TO THE COMPANY’S HUMAN CAPITAL PERFORMANCE - Sondakh, Oliandes; Magdalena, Renna (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This study investigates the relationship between the quality culture fostered by implementing MBNQA quality management and human capital performance in one of Indonesia's largest industrial gas companies. One hundred eight employees with a level of management below that of a manager completed the survey questionnaires. Analyzing the relationship between seven variables of quality culture based on the Malcolm Baldrige Criteria for Performance Excellence, namely Leadership, Strategic Planning, Customer Focus, Measurement, Analysis and Knowledge Management, Focus on Manpower, Process Management, and Results, multiple linear regression techniques were employed. The study hypothesizes a statistically significant relationship between Customer Focus, Measurement Analysis and Knowledge Management, Focus on Human Resources, Process Management and Human Capital Performance. The study's findings suggest that the four quality cultures - Customer Focus, Measurement, Analysis, Knowledge Management, Focus on Human Resources, and Process Management - can be utilized effectively within the context of an industrial gas company to improve Human Capital performance. Few studies have examined the relationship between quality culture and the human capital performance of low-level managerial employees at Indonesia Gas Company, so the results are significant.